The adoption of green innovation in the scottish construction industry context - Hashim, Rushanim; Salleh, Nurul Azita (School of Technology Management and Logistics (STML), 2019)
The growing interest in environmental innovation has led to an increase in the number of research studies around that area in different industries (Dutz & Sharma, 2012). The construction industry is a critical industry for the study of environmental- or sustainability related issues, considering that, it is responsible for some of the most serious impacts on the environment. Indeed, there is a growing concern regarding environmental impacts resulting from construction activities. By comparison with other industries, its activities are considered as making a major contribution to environmental problems (Ball, 2002; Tam, Tam & Tsui, 2004; Tam & Tam, 2008). In the United Kingdom (UK), specifically, the construction sector contributed 11.2% of the total of UK greenhouse gas emissions in 2013 (Office for National Statistics, 2015) while around 420 million tonnes of construction material is consumed by the construction industry each year, whereby approximately 120 million tonnes is wasted (EISC, 2012). It shows that, by its nature, construction is not an environmentally-friendly activity. Conversely, the construction industry plays a vital role in meeting the needs of society and enhancing the quality of life. Its activities directly affect the nature, function and appearance of the place in which people live. In addition, it contributes to a better standard of living by offering employment to people all over the world. Specifically, the UK construction industry employs 2.1 million people (Rhodes, 2015), accounting for 6.3% of total UK employment in 2014. The industry’s output was increased to £92 billion (6.4% of the total economy) in 2014 (Office for National Statistics, 2015), which makes a valuable contribution to the UK economy. Hence, the economic significance of the construction industry cannot be underestimated.